2018
DOI: 10.1159/000490742
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Cognitive Behavioral Therapy for Chronic Stress: A Randomized Controlled Trial

Abstract: Background: Prolonged exposure to stress can lead to substantial suffering, impairment and societal costs. However, access to psychological treatment is limited. Internet-based cognitive behavioral therapy (ICBT) can be effective in reducing symptoms of stress, but little is known of its effects in clinical samples. The aim of this study was to investigate the efficacy of ICBT for patients suffering from chronic stress, operationalized as adjustment disorder (AD) and exhaustion disorder (ED). Methods: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 39 publications
7
71
0
Order By: Relevance
“…As there are very few previously published randomized trials of psychological treatments for stress‐related disorders (Perski et al ., ), we view the results of this study regarding effects of CBT on symptom reduction as very promising. The present treatment, CBT for stress‐related disorders, has been further studied as Internet delivered CBT and effects on reduced symptoms were comparable (Lindsäter et al ., ). We therefore consider that this type of CBT for AD and ED could contribute to the evidence base for effective treatments of these disorders.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…As there are very few previously published randomized trials of psychological treatments for stress‐related disorders (Perski et al ., ), we view the results of this study regarding effects of CBT on symptom reduction as very promising. The present treatment, CBT for stress‐related disorders, has been further studied as Internet delivered CBT and effects on reduced symptoms were comparable (Lindsäter et al ., ). We therefore consider that this type of CBT for AD and ED could contribute to the evidence base for effective treatments of these disorders.…”
Section: Discussionmentioning
confidence: 97%
“…As no evidence‐based treatments exist for AD and ED, these disorders were treated with a CBT protocol that has been developed by our research group and tested in clinical practice since 2007. The treatment has been included in three randomized trials as face‐to‐face treatment (present study: Salomonsson et al ., ), stepped care with guided self‐help and face‐to‐face treatment (Salomonsson et al ., ), and as an Internet‐based treatment (Lindsäter et al ., ). The treatment is based on a model assuming that these disorders are maintained by a deficit of recuperation (Geurts & Sonnentag, ; Lisspers, Almén, & Sundin, ) that can be caused by for example difficulties to relax, extensive rumination, or aversive consequences of relaxing (e.g., a person may feel shame or guilt if taking a rest instead of working or helping friends or family).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, meta-analyses of diagnosed samples have failed to find superior improvements of CBT compared to control conditions for both adjustment disorder 100 and exhaustion disorder 101 . Although recent randomized trials have found promising results of CBT for these disorders 102,103 , the effectiveness of CBT remains uncertain.…”
Section: Effectiveness Of Cbtmentioning
confidence: 99%